ANALISIS SEMIOTIK CHARLES SANDERS PEIRCE TERHADAP LOGO PROVINSI GORONTALO - Siska Udilawaty; Apsari Dj.Hasan (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
This study discusses the meaning contained in the logo of the Province of Gorontalo in semiotic analysis. Logo is the identity of an institution that represents the history and culture of the institution while semiotics is the science of reading signs both verbally and visually, visual forms make the vision and mission as well as identity reflected in a logo. Just like the regional logo of Gorontalo Province which has various meanings of signs and symbols that reflect the area, for example, the Padi and cotton symbols are inspired by the city government logo which means depicting prosperity and others. There is also an oval pattern in the logo taken from the eggs of the Maleo bird, which is endemic to Gorontalo. There is the fort of Otana and pictures of books taken from our philosophy "adat based on sara', sara' based on the book of Allah. The purpose of the study was to describe and analyze what the meaning of the symbols in the logo of the Gorontalo Province were. The research used semiotic analysis of Charles Sanders Peirce. Semiotics departed from three main elements, which Peirce called the triangle theory of meaning, namely: signs, objects, and interpretants. The meaning of the logo can be studied scientifically with semiotic theory. In Peirce's study, symbols are divided into 3 categories: icons, indexes, and symbols. To analyze the meaning of symbols, Peirce uses 3 semiotic terms: representamen which is a symbol, semiotic object which is a real object of symbol reference, and interpretant which states the relationship between representamen and semiotic objects. Benefits of this research To add scientific insight in the field of linguistics, especially to the use of semiotic theory and to find out creative strategies in promotional activities of a government institution so that they can build a brand in the eyes of the public. The results of this study determine the meaning of the signs on the regional symbols of Gorontalo province. The output of this research is a scientific paper published in an accredited national journal.This study discusses the meaning contained in the logo of the Province of Gorontalo in semiotic analysis. Logo is the identity of an institution that represents the history and culture of the institution while semiotics is the science of reading signs both verbally and visually, visual forms make the vision and mission as well as identity reflected in a logo. Just like the regional logo of Gorontalo Province which has various meanings of signs and symbols that reflect the area, for example, the Padi and cotton symbols are inspired by the city government logo which means depicting prosperity and others. There is also an oval pattern in the logo taken from the eggs of the Maleo bird, which is endemic to Gorontalo. There is the fort of Otana and pictures of books taken from our philosophy "adat based on sara', sara' based on the book of Allah. The purpose of the study was to describe and analyze what the meaning of the symbols in the logo of the Gorontalo Province were. The research used semiotic analysis of Charles Sanders Peirce. Semiotics departed from three main elements, which Peirce called the triangle theory of meaning, namely: signs, objects, and interpretants. The meaning of the logo can be studied scientifically with semiotic theory. In Peirce's study, symbols are divided into 3 categories: icons, indexes, and symbols. To analyze the meaning of symbols, Peirce uses 3 semiotic terms: representamen which is a symbol, semiotic object which is a real object of symbol reference, and interpretant which states the relationship between representamen and semiotic objects. Benefits of this research To add scientific insight in the field of linguistics, especially to the use of semiotic theory and to find out creative strategies in promotional activities of a government institution so that they can build a brand in the eyes of the public. The results of this study determine the meaning of the signs on the regional symbols of Gorontalo province. The output of this research is a scientific paper published in an accredited national journal.